Metal nanoinks as chemically stable surface enhanced scattering (SERS) probes for the analysis of blue BIC ballpoint pens. Issue 22 (24th May 2017) - Alyami, A.; Saviello, D.; McAuliffe, M. A. P.; Mirabile, A.; Lewis, L.; Iacopino, D.
Abstract : Metal nanoinks constituted by Ag nanoparticles and Au nanorods were employed as probes for the Surface Enhanced Raman Scattering (SERS) analysis of a blue BIC ballpoint pen. Abstract : Metal nanoinks constituted by Ag nanoparticles and Au nanorods were employed as probes for the Surface Enhanced Raman Scattering (SERS) analysis of a blue BIC ballpoint pen. The dye components of the pen ink were first separated by thin layer chromatography (TLC) and subsequently analysed by SERS at illumination wavelengths of 514 nm and 785 nm. Compared to normal Raman conditions, enhanced spectra were obtained for all separated spots, allowing easy identification of phthalocyanine Blue 38 and triarylene crystal violet in the ink mixture. A combination of effects such as molecular resonance, electromagnetic and chemical effects were the contributing factors to the generation of spectra enhanced compared to normal Raman conditions. Enhancement factors (EFs) between 5 × 10 3 and 3 × 10 6 were obtained, depending on the combination of SERS probes and laser illumination used. In contrast to previous conflicting reports, the metal nanoinks were chemically stable, allowing the collection of reproducible spectra for days after deposition on TLC plates. In addition and in advance to previously reported SERS probes, no need for additional aggregating agents or correction of electrostatic charge was necessary to induce the generation of enhanced SERS spectra.